Training the design skills based on the Agire educativo paradigm. The laboratories at the Sciences of Education Degree courses (L19) - Loredana Perla; Laura Sara Agrati (Firenze University Press, 2020)
The design is assumed as the ability to adapt the models learned to the context and the situations in an intelligent way and a complex competence within the Agire educativo (Perla & Riva, 2016) since it implies global-analytical approach, clinical intuition and know-how. The article deals with how to train this complex competence in view of the explanatory models - Terzo educativo (Perla, 2016a) and Finalità-Variabili-Percorso (F-V-P) (Rossi & Toppano, 2009) in the specific abductive component of them, and describes the organizational structure as well as the operating devices of the laboratories (EduLabo and Interventions on developmental disabilities) held at the Science of Education Degree courses, at the University of Bari and Giustino Fortunato Open University. In this way, some clarifications regarding the complex nature of the design ability, exemplifications of the didactically educational method as well as arguments on the didactic coordination of the Science of Education Degree courses are offered.   Formare l'abilità progettuale alla luce del paradigma dell'agire educativo. I laboratori nei CdL-19 Il lavoro assume la progettazione come capacità di adattare in maniera intelligente modelli appresi in ragione del contesto e delle situazioni e la rilancia come competenza complessa dell'Agire educativo (Perla & Riva, 2016) che implica approccio globale e analitico, intuizione clinica e tecnicalità. L'articolo pone la questione su come formare tale competenza complessa attraverso la ripresa dei modelli esplicativi del Terzo educativo (Perla, 2016) e della Finalità-Variabili-Percorso (F-V-P) (Rossi & Toppano, 2009), nella specifica componente abduttiva, e descrive l'impianto organizzativo nonché i dispositivi operativi dei laboratori (EduLabo e Interventi nelle disabilità dello sviluppo) adottati nei CCdSS Scienze dell'educazione e della formazione dell'Università degli Studi di Bari e Scienze dell'Educazione dell'Università Telematica Giustino Fortunato. Vengono, così, offerti alcuni possibili chiarimenti circa il carattere complesso dell'abilità progettuale, un'esemplificazione di metodo didatticamente educativo nonché argomenti sulla necessità di una regia didattica dei CdL-19.